2021
DOI: 10.4102/sajhrm.v19i0.1454
|View full text |Cite
|
Sign up to set email alerts
|

Job performance: Working conditions of urban teachers in Zimbabwean schools

Abstract: Orientation: For Zimbabwean schools to deliver quality education in this competitive and hyperinflationary environment, teachers must be paid a living wage, which is commensurate with their noble profession to spruce up their public image and retain the best.Research purpose: The research established the Zimbabwean urban teachers’ working conditions, which affected their job performance and proffered remedies.Motivation for the study: Schools with favourable working conditions attracted, developed and retained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Professional image refers to the beginning of the employee's professional experience, which is gradually internalized in the formation of professional behavior. After the profession interacts with its environment, the public forms an image of the profession in its best state [22]. An Iranian study showed that the general public's attitude towards the nursing profession is not positive.…”
Section: Professional Imagementioning
confidence: 99%
“…Professional image refers to the beginning of the employee's professional experience, which is gradually internalized in the formation of professional behavior. After the profession interacts with its environment, the public forms an image of the profession in its best state [22]. An Iranian study showed that the general public's attitude towards the nursing profession is not positive.…”
Section: Professional Imagementioning
confidence: 99%
“…También puede ser definido como la respuesta con éxito a los altos mandos, subordinados, compañeros de trabajo y clientes en las organizaciones y lograr objetivos organizacionales específicos [9]. Ngwenya [13] lo percibe como el valor total esperado para la organización del comportamiento discreto durante un tiempo estándar. Del mismo modo, lo considera como: "la suma total de la ejecución de las tareas asignadas por parte de los trabajadores.…”
Section: Desempeño Laboralunclassified